Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1103/physrevlett.97.216803
|View full text |Cite|
|
Sign up to set email alerts
|

Energy Gaps in Graphene Nanoribbons

Abstract: Based on a first-principles approach, we present scaling rules for the band gaps of graphene nanoribbons (GNRs) as a function of their widths. The GNRs considered have either armchair or zigzag shaped edges on both sides with hydrogen passivation. Both varieties of ribbons are shown to have band gaps. This differs from the results of simple tight-binding calculations or solutions of the Dirac's equation based on them. Our ab initio calculations show that the origin of energy gaps for GNRs with armchair shaped … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

158
2,465
11
8

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 4,618 publications
(2,697 citation statements)
references
References 40 publications
158
2,465
11
8
Order By: Relevance
“…For example, ballistic room-temperature transistors [3][4][5] and carbon-based spintronic devices [6][7][8][9][10] are two tantalizing possibilities which could one day be realized in a graphene nanodevice. First though, a reliable method must be found to controllably produce graphene nanostructures with specific sizes, geometries, and defined crystallographic edges.…”
mentioning
confidence: 99%
“…For example, ballistic room-temperature transistors [3][4][5] and carbon-based spintronic devices [6][7][8][9][10] are two tantalizing possibilities which could one day be realized in a graphene nanodevice. First though, a reliable method must be found to controllably produce graphene nanostructures with specific sizes, geometries, and defined crystallographic edges.…”
mentioning
confidence: 99%
“…[51][52][53] For example, it is known that mechanical straining can alter the band gaps of graphene nanoribbons significantly. [51,[54][55][56][57][58][59] Similarly, it has also been shown that straining can change the band gaps for h-BN nanoribbons [15,18] and large area h-BN. [60] We note that in reference, [60] the authors investigated the bandgap as a function of strain to the strain where the bandgap eventually approaches zero.…”
mentioning
confidence: 99%
“…In particular, for zigzag graphene nanoribbons (ZGNRs) terminated with one hydrogen atom on each zigzag edge, there are quite a few localized edge states near the Fermi energy level on both edges. Such localized edge states can lead to a spin induced energy gap [113] providing a significant effect on the electronic and transport properties [114]. The electronic and transport properties are thus very sensitive to the atomic structures and chemical modification of the edges.…”
Section: Graphenementioning
confidence: 99%